Acompanhamento longitudinal de lesões cariosas inativas: resultados após 13 anos - Castro, Nathália Costa de (2024)
The prospective cohort study that forms part of this dissertation aimed to evaluate the clinical behavior of dental caries lesions diagnosed as inactive on the occlusal surfaces of permanent molars, defining their risk for progression after 13 years. Volunteers aged between 7 and 15 years were initially examined for the presence and activity of caries lesions on the occlusal surfaces of molars (modified CPO index), the accumulation and distribution of occlusal biofilm and the eruptive stage of these teeth. To fulfill the inclusion criteria, the schoolchildren had to be classified as caries-inactive and have at least one sound permanent molar and one permanent molar with an inactive caries lesion (n=258). After 1 and 4-5 years (phases I and II, respectively), a new clinical examination was carried out using the same criteria as before and a new comparative analysis was made. After 13 years (phase III), the patients were examined once again regarding the clinical status of the caries lesions previously diagnosed as inactive (n=102). In this new phase, examinations were performed in a dental unit or through home visits by three examiners. The examiners were calibrated for all criteria adopted and intra- and inter-examiner unweighted Cohen's kappa values ≥ 0.85 were obtained. Two different outcomes were defined: progression by activity, defined as the presence of an active lesion, filling or extraction at the follow-up examination, and progression by severity, defined as the presence of a dentin cavity, filling or extraction at the follow-up examination. The statistical analysis used logistic regression models, which were adjusted using generalized estimating equations due to the presence of clustered data. Odds ratios (OR) and their respective 95% confidence intervals (CI) were estimated. In this third phase of the study, the average age of the volunteers was 26.5 (± 3.0) years, of which 55.9% (n=57) were male and 44.1% (n=45) female. Each participant contributed an average with 6 sample units, ranging from 2 to 10 teeth. A total of 601 teeth were included in the analysis. For the activity criterion, the progression rates found were 8.7% (n=27) for sound sites and 18.8% (n=55) for caries lesions initially diagnosed as inactive (p<0.05). For the severity criterion, the respective rates were 5.8% (n=18) and 13.4% (n=39) (p<0.001). The risk analysis showed that inactive lesions presented a risk for progression around twice as high as sound surfaces, both for the activity criterion (OR=2.01, 95% CI =1.23-3.52) and for the severity criterion (OR=2.49, 95% CI =1.42-4.35). This study showed that the vast majority of lesions initially diagnosed as inactive did not show disease progression over the 13-year observational period. However, they showed higher progression rates when compared to sound occlusal surfaces.